2008
DOI: 10.3801/iafss.fss.9-1213
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of pyrolysis model parameters for solid materials using thermogravimetric data

Abstract: Determination of the material parameters is one of the key challenges of numerical fire simulation attempting to predict, rather than prescribe the heat release rate. In this work, we use common fire simulation software and genetic algorithms to estimate the kinetic reaction parameters for wood components, birch wood, PVC and black PMMA. Parameters are estimated by modelling thermogravimetric experiments and minimizing the error between the experimental and numerical results. The implementation and choice of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 4 publications
1
35
0
1
Order By: Relevance
“…Both kinetic and thermal parameters were estimated using a genetic algorithm minimizing the error between the experimental and simulated data [13]. The kinetic coefficients were estimated from thermogravimetric (TGA) experiments in an N 2 atmosphere at several heating rates.…”
Section: Materials Model For Birch Woodmentioning
confidence: 99%
“…Both kinetic and thermal parameters were estimated using a genetic algorithm minimizing the error between the experimental and simulated data [13]. The kinetic coefficients were estimated from thermogravimetric (TGA) experiments in an N 2 atmosphere at several heating rates.…”
Section: Materials Model For Birch Woodmentioning
confidence: 99%
“…The GA parameters in this work are the same as used in Ref. [6] except for the mutation rate that was set to 0.25.…”
Section: Model Parametersmentioning
confidence: 99%
“…This method, utilizing e.g. genetic algorithm (GA) as an optimization method, has been used in many of the recent works [4][5][6][7]. Genetic algorithms are based on the idea of survival of the fittest.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The heats of reaction, Δh r were found to be endothermic and are tabulated in Table 1. Matala et al in references [11] and [12] investigated the decomposition in nitrogen of birch, oak, pine, PVC, PMMA, graphite and various wood components such as cellulose, lignin and xylan. The authors reported that endothermic heat flow was obtained during the decomposition and the heat of reaction for cellulose and birch was 482 and 230 J/g respectively.…”
Section: First Reactionmentioning
confidence: 99%